Non-Alcoholic Fatty Liver Disease with Endocrine Diseases in Children and Adolescents Abstract - Sevara, Begmatova; Xalbayeva, Zubayda (American Journal of Bioscience and Clinical Integrity, 2026)
Non-alcoholic fatty liver disease (NAFLD) is now the most common chronic liver condition among children, heavily linked to obesity and endocrine malfunction. In this context, comorbidities of NAFLD together with endocrine diseases such T2DM, insulin resistance (IR), hypothyroidism, polycystic ovary syndrome (PCOS), growth hormone deficiency and Cushing's syndrome significantly increase the risk of metabolic impairments as well as NAFLD progression. The purpose of the present study was to investigate clinical, and metabolic features associated with NAFLD in children and adolescents having concomitant endocrine diseases, assess laboratory and imaging profiles, and determine their effects on the severity of a disease. Cross sectional observational design was used to measure anthropometry, hormones, lab indices and liver of Ultrasound. The findings show an interaction of insulin resistance, dyslipidemia, hormones and hepatic steatosis. Children with concomitant endocrine pathology had higher alanine aminotransferase, hepatic fat content and systemic inflammation markers than those with normal hormonal studies. Early recognition, together with a more comprehensive management approach is necessary to avoid progression to non-alcoholic steatohepatitis and consequential long-term cardiometa*bolic health implications. Nonalcoholic fatty liver disease in children and adolescents has emerged as a major metabolic comorbidity associated with endocrine dysregulation. Hepatic steatosis and endocrinopathies (frequently in the form of obesity-related insulin resistance, type 2 diabetes mellitus, thyroid disease, growth hormone deficiency, hypercortisolism and polycystic ovary syndrome) coexist in many instances and have considerable effect on the onset, progression and outcome of these conditions. This paper reviews the clinical manifestations, metabolic disturbances, and functional hepatic alterations encountered in children with hepatopathy occurring simultaneously with endocrinopathy. Evidence suggests that the imbalance of hormones further aggravates lipid deposition in hepatocytes, inflammation and fibrotic alteration. Administrative health data Children with endocrine co-morbid conditions show more significant biochemical changes, such as elevated transaminases of the liver, dyslipidemia and disturbed glucose metabolism. An early detection of endocrine risk factors may provide an opportunity for early intervention with a focus on restoring metabolic stability and preventing severe liver damage. Comprehensive, collaborative and integrated management approaches are required to optimize long-term outcomes and minimize cardiometabolic risk in this vulnerable population.